Developing Pragmatic Competence Through Project-Based Learning: Insights from Indonesian EFL Students’ Interactions with Foreign Tourists: Mengembangkan Kompetensi Pragmatik melalui Project-Based Learning: Temuan dari Interaksi Siswa EFL Indonesia dengan Turis Asing - I Gede Neil Prajamukti Wardhana; I Gusti Nyoman Putra Kamayana; Ni Luh Desy Suari Dewi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Developing pragmatic competence is essential for EFL learners, especially in contexts where real communication opportunities are limited. This study investigates how Project-Based Learning (PBL) supports the development of pragmatic competence among Indonesian EFL students during real-life speaking interactions with foreign tourists at Double Six Beach, Bali. The project activity focused on the theme “Getting to Know Each Other.” Using a qualitative descriptive design, the study analyzed speech acts produced by two learner groups: kids (9–12 years old) and teenagers (14–16 years old). Data were collected from video recordings of student–tourist interactions and examined using Searle’s (1976) speech act taxonomy and Hymes’ (1972) notion of pragmatic competence. Findings show that both groups were able to perform a range of speech acts, including greetings, asking for information, sharing personal details, expressing gratitude, and managing conversational turns. Overall, the study shows that Project-Based Learning provides a useful way to develop pragmatic competence by involving students in meaningful and authentic communication outside the classroom.